Electric field stimulation directs target-specific axon regeneration and partial restoration of vision after optic nerve crush injury - Timothy Kim; Ege Iseri; Micalla G. Peng; Sasha Medvidovic; Timothy Silliman; Pooyan Pahlavan; Gengle Niu; Connie Huang; Anahit Simonyan; Javad Pahnahad; Petcy Yao; Phillip Lam; et al. (PLoS ONE, 2025)
Failure of central nervous system (CNS) axons to regenerate after injury results in permanent disability. Several molecular neuro-protective and neuro-regenerative strategies have been proposed as potential treatments but do not provide the directional cues needed to direct target-specific axon regeneration. Here, we demonstrate that applying an external guidance cue in the form of electric field stimulation to adult rats after optic nerve crush injury was effective at directing long-distance, target-specific retinal ganglion cell (RGC) axon regeneration to native targets in the diencephalon. Stimulation was performed with asymmetric charged-balanced (ACB) waveforms that are safer than direct current and more effective than traditional, symmetric biphasic waveforms. In addition to partial anatomical restoration, ACB waveforms conferred partial restoration of visual function as measured by pattern electroretinogram recordings and local field potential recordings in the superior colliculus—and did so without the need for genetic manipulation. Our work suggests that exogenous electric field application can override cell-intrinsic and cell-extrinsic barriers to axon regeneration, and that electrical stimulation performed with specific ACB waveforms may be an effective strategy for directing anatomical and functional restoration after CNS injury.